Agglomeration economies in Australian cities : productivity benefits of increasing urban density and accessibility - Trubka, Roman Lubor (Curtin University, 2011)
Agglomeration economies are a subject that has been gaining a significant amount of interest in the realms of policy and urban planning. The term refers to the externalities that arise out of the interactions of firms and employees, which are made possible by spatial proximity. Although empirical studies measuring the impacts of agglomeration economies on firm and employment productivity have been conducted for a number of nations around the world, no such study has yet has been conducted for Australia or Australian cities. The research embodied in this thesis seeks to measure the magnitude by which employment productivity in a range of industries in Australian cities is influenced by agglomeration and offers a method for these estimations that is suitable given the types of data collected and made available nationally. Furthermore, analyses are conducted on a wider range of industries than reported by existing works on the subject.Analyses are carried out primarily on Sydney and Melbourne; however, one analysis incorporates all eight capital cities. The rationale behind conducting analyses on two cities is to allow comparisons to be made, thus providing a means for validating the city-specific results and contributing to an understanding of whether elasticity estimates can be generalized within the nation. Topics such as the relative importance of urbanization versus localization economies are addressed as well as the issue of endogeneity. Current state-of-the-art practices in incorporating the benefits of agglomeration economies in transport project appraisal in Australia are reviewed. Additionally, the outcomes of the empirical analyses are drawn on in a discussion of the relevance of agglomeration economies for sustainability and urban planning.The findings show industry-specific employment productivities do benefit significantly from agglomeration and at magnitudes comparable to international studies. The devised econometric model proves effective at estimating agglomeration impacts and can be replicated for other Australian cities and regions – a suggested alternative to generalizing industry-specific elasticities as evidence exists that they are likely to differ for at least some industries. The evidence of agglomeration economies working in Australian cities becomes a powerful companion rationale for considering density and quality public transport services which are frequently at the centre of urban sustainability strategies.